Bovine three-portion pericardial patch for reconstruction of the aorto-mitral curtain in infective endocarditis - Atsushi Hiromoto; Shun-Ichiro Sakamoto; Yasuo Miyagi; Takashi Nitta (Surgical Case Reports, 2019)
Abstract Background Surgery for infective endocarditis involving the aorto-mitral curtain (AMC) is challenging and requires extensive incisions and complex reconstruction procedures. However, in patients with preserved aortic annulus, reconstruction of the AMC is possible using a simple technique with limited incisions. Case presentation A handmade bovine three-portion pericardial patch was used to reconstruct the AMC in a patient with severe endocarditis requiring double valve replacement; the technique allowed for steady anchorage of prosthetic valves without additional incisions other than conventional aortotomy and atriotomy. Postoperative echocardiography revealed normal cardiac function and no significant perivalvular leakage. The patient displayed complete recovery and was discharged on postoperative day 33. The patient was symptom-free at his 1-year follow-up and displayed normal laboratory and echocardiographic findings. Conclusion The bovine three-portion pericardial patch is useful for reconstructing the AMC in patients with infective endocarditis accompanied by preserved aortic annulus.